2007
DOI: 10.1055/s-2007-966753
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon colonoscopy after failed conventional colonoscopy: a pilot series with a new instrument

Abstract: Double-balloon colonoscopy enables full colonic examination in almost all patients with a previous incomplete colonoscopy. The overtube should be used in most cases. The use of fluoroscopic assessment of scope progression could be reduced further with increasing experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 12 publications
5
51
0
1
Order By: Relevance
“…We previously reported that the use of a colonoscope with an outer diameter of 9.2 mm and an effective length of 1600 mm (CF-PQ260L ® , Olympus Co., Tokyo, Japan) allowed total colonoscopy to be performed in the majority of patients in whom scope insertion was precluded by an elongated colon and adhesions [13] . Preliminary studies have suggested that the use of a guide-wire-directed endoscope or a spiral overtube can facilitate colonoscope insertion when difficulty is en-useful [21] . In addition to diagnostic procedures such as biopsy, SBE allowed colorectal polyps to be endoscopically resected with no problems or complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the use of a colonoscope with an outer diameter of 9.2 mm and an effective length of 1600 mm (CF-PQ260L ® , Olympus Co., Tokyo, Japan) allowed total colonoscopy to be performed in the majority of patients in whom scope insertion was precluded by an elongated colon and adhesions [13] . Preliminary studies have suggested that the use of a guide-wire-directed endoscope or a spiral overtube can facilitate colonoscope insertion when difficulty is en-useful [21] . In addition to diagnostic procedures such as biopsy, SBE allowed colorectal polyps to be endoscopically resected with no problems or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon endoscopy has previously been reported to be useful for colonoscopy in patients with a history of difficulty in colonoscope insertion [16][17][18][19][20][21][22][23] . Most studies used a DBE, but two studies conducted in the United State and Holland reported the results of SBE [22,23] .…”
Section: Applicationsmentioning
confidence: 99%
“…9 Some previous studies have described techniques and yields of repeat colonoscopy in patients with prior incomplete colonoscopies 6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Our series has several strengths, including its large size (this series accounts for more than half of all reported cases) and referral of all cases from other gastroenterologists and surgeons.…”
mentioning
confidence: 99%
“…There have been many case reports describing the utility of BE for completion of colonoscopy after an incomplete examination with a conventional colonoscope [5][6][7][8] . BE is useful because it can hold and shorten a complicated and elongated bowel segment, and therefore can be used in patients with difficult colonoscopies.…”
Section: Successfullymentioning
confidence: 99%